2022
DOI: 10.5194/acp-2022-408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation and impacts of nitryl chloride in Pearl River Delta

Abstract: Abstract. Here we present a field measurement of ClNO2 (nitryl chloride) and N2O5 (dinitrogen pentoxide) by a state-of-the-art instrument at a regional site in Pearl River Delta during a photochemical pollution season from Sept. 26th to Nov. 17th, 2019. Three patterns of air masses are sampled during this campaign, including the dominating air masses from north and northeast urban regions (Type A), the southeast coast (Type B) and the South China Sea (Type C). The concentration of ClNO2 and N2O5 were observed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A poor prognosis and resistance to chemotherapy are the two most important characteristics of this disease. Recently, Yang et al reported capsaicin-induced cell death in human bladder cancer T24 cells through calcium entry-dependent ROS production and mitochondrial depolarization [71]. Likewise, Chen et al also demonstrated capsaicin-induced cell cycle arrest by inhibiting cyclin-dependent-kinase in 5637 bladder carcinoma cells [72].…”
Section: Bladder Cancermentioning
confidence: 99%
“…A poor prognosis and resistance to chemotherapy are the two most important characteristics of this disease. Recently, Yang et al reported capsaicin-induced cell death in human bladder cancer T24 cells through calcium entry-dependent ROS production and mitochondrial depolarization [71]. Likewise, Chen et al also demonstrated capsaicin-induced cell cycle arrest by inhibiting cyclin-dependent-kinase in 5637 bladder carcinoma cells [72].…”
Section: Bladder Cancermentioning
confidence: 99%